RNAseq revealed the important gene pathways controlling adaptive mechanisms under waterlogged stress in maize - Kanika Arora (Nature Portfolio, 2017)
Abstract Waterlogging causes yield penalty in maize-growing countries of subtropical regions. Transcriptome analysis of the roots of a tolerant inbred HKI1105 using RNA sequencing revealed 21,364 differentially expressed genes (DEGs) under waterlogged stress condition. These 21,364 DEGs are known to regulate important pathways including energy-production, programmed cell death (PCD), aerenchyma formation, and ethylene responsiveness. High up-regulation of invertase (49-fold) and hexokinase (36-fold) in roots explained the ATP requirement in waterlogging condition. Also, high up-regulation of expansins (42-fold), plant aspartic protease A3 (19-fold), polygalacturonases (16-fold), respiratory burst oxidase homolog (12-fold), and hydrolases (11-fold) explained the PCD of root cortical cells followed by the formation of aerenchyma tissue during waterlogging stress. We hypothesized that the oxygen transfer in waterlogged roots is promoted by a cross-talk of fermentative, metabolic, and glycolytic pathways that generate ATPs for PCD and aerenchyma formation in root cortical cells. SNPs were mapped to the DEGs regulating aerenchyma formation (12), ethylene-responsive factors (11), and glycolysis (4) under stress. RNAseq derived SNPs can be used in selection approaches to breed tolerant hybrids. Overall, this investigation provided significant evidence of genes operating in the adaptive traits such as ethylene production and aerenchyma formation to cope-up the waterlogging stress.